Paying the Trial Tax: Race, Guilty Pleas, and Disparity in Prosecution. (May 2020) - Testa, Alexander; Johnson, Brian D.
The vast majority of criminal cases are disposed of through guilty pleas, yet relatively little empirical research focuses on the factors that are related to whether a defendant pleads guilty or goes to trial. The current work investigates this issue, analyzing three recent years of data from the Maryland Commission on Criminal Sentencing Policy. It examines predictors of guilty plea and trial dispositions as well as key differences among different types of guilty pleas. Findings indicate that Black and Latino defendants are substantially less likely to plead guilty, and that these differences are most pronounced for nonnegotiated guilty pleas. Little evidence emerges for gender disparities or for compound disadvantages associated with young, male, minority defendants. Results are discussed as they relate to contemporary theoretical perspectives on racial differences in perceived legitimacy and trust in the criminal justice system.